PENERAPAN TEKNIK THINK PAIR SHARE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PADA MATA KULIAH READING COMPREHENSION - Yani, Titik Hardewi; Sesmiyanti, Sesmiyanti (STKIP PGRI Sumatera Barat, 2014)
This research problem comes from low of students’ score of reading comprehension at English program academic year 2012/2013. It could be seen from some students failed in reading comprehension I. In order to researcher would do classroom action research by applying Think Pair Share technique to improve students reading comprehension on reading II. Purpose of this research were to describe applying Think Pair Share technique on reading comprehension of English program and knowing how can Think Pair Share improve students’ reading comprehension. In collecting data, researcher used qualitative data that consist of observation sheet, field note, and interview. In quantitative data, she used tasks and tests. In making note about what happened in this research, she helped by collaborator who teach reading comprehension too in English Department. This classroom action research consisted of two cycles; each of cycles consisted of four meeting. Three meeting did treatments, and one meeting for test. Related to finding of this research, Think Pair Share technique could improve reading comprehension. In addition, the factor that influence students’ learning by applying this technique were interesting technique, interesting topic of learning material then lecturer guiding on students in understanding learning material. The improvement of students’ learning could be proved on students’ score in each cycles. Mean score students’ reading comprehension for the first cycle was 63.8, then second cycle was 73.3. This research can be concluded that classroom action research by applying Think Pair Share technique could improve students’ reading comprehension on Reading II course at English program STKIP PGRI Sumatera Barat.